PENGUKURAN KINERJA REKSA DANA PADA REKSA DANA SYARIAH DAN REKSA DANA KONVENSIONAL DI INDONESIA PERIODE 2008 – 2018 - Zulfiyah Azmi; Bayu Arie Fianto (Universitas Airlangga, 2019)
This research measured and compared the performance between Islamic mutual funds and conventional mutual funds using Sharpe Ratio, Treynor Index, Jensen Alpha, Modigliani Measure, Appraisal Ratio, and Adjusted Sharpe Ratio. This research used quantitative approach with panel data that was measured by using different test and it aimed to find out the comparation of the samples. This research used Net Asset Value (NAV), Joint Stock Price Index, BI Rate to find out return and risk that will be implemented on the measured methods. The results of the research based on T-test are that there is no significant difference of performance between Islamic mutual funds and conventional mutual funds, except the Appraisal Ratio method that shows the difference on Islamic mutual funds that has a better performance.Keywords: Sharpe Ratio, Treynor Index, Jensen Alpha, Modigliani Measure, Appraisal Ratio, Adjusted Sharpe RatioREFFERENCESAbdul Halim. (2005). Analisis Investasi Edisi 2. Jakarta: Salemba Empat.Adrian Sutedi. (2011). Pasar Modal Syariah Sarana Investasi Keuangan Berdasarkan Prinsip Syariah. Jakarta : Sinar Grafika.Al-Bahar, J,.F. Crandall, K.C. (1990). Systematic Risk Management Approach for Construction Project. Journal of Construction Engineering Management. ASCE, 116 (3) 533-545.Bodie, Zvi., Kane, Alex., Markus, Alan J., dan Jain, Ravi. (2010). Investments. Buku 1 dan 2. Terjemahan oleh, Zulaini Dalimunthe dan Budi Wibowo. Jakarta: Salemba Empat.COSO. (2004). Enterprise risk management– integrated framework. Committee of Sponsoring Organizations.Devaney,M, Morillon, T & Weber, W. 2016. Mutual fund efficiency andtradeoffs in the production ofrisk and return.Managerial Finance.Vol. 42. No: 3. pp. 225-243.Drobetz, Wolfgang and Kohler, Friederike. (2002). The Contribution of Asset Allocation Policy to Portfolio Performance. Working Paper. No. 2/02, Basel: WWZ/Departement of Finance University of Basel.Eduardus Tandelilin. (2001). Analisis Investasi dan Manajemen Portofolio Edisi Pertama. Yogyakarta: BPFE-Yogyakarta.Mansor, Fadillah, and M Ishaq Bhatti. (2011). Risk and Return Analysis on Performance of the Islamic Mutual Funds : Evidence from Malaysia. Global Economy and Finance Journal, 4, 19– 31.Modigliani, F., & Modigliani, L. (1997). Risk-adjusted performance. Journal of Portfolio Management, 23(2), 45–54.Muhammad Firdaus. Et. Al. (2005). Investasi Halal di Reksa dana Syariah. Jakarta: Renaisa.Shamsher, M., & Annuar, M. N. (1995). The performance of unit trusts in Malaysia: Some evidence. Capital Market Review, 3, 51–64.Sharpe, William F. (1966). Mutual Fund Performance. Journal of Business, V. 39, Part 2: pp 119-138.Sudarsono, Heri. (2003). Bank dan Lembaga Keuangan Syariah. Yogyakarta: EKONISIA.Sugiyono. (2015). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif dan R&D). Penerbit CV. Alfabeta: Bandung. Sukirno, Sadono. (2011). Makro Ekonomi Teori Pengantar Edisi Ketiga. Rajawali Pers, Jakarta.Sunariyah. (2011). Pengantar pengetahuan pasar modal. Edisi keenam. UPP STIM YKPN. Yogyakarta.Suryani dan Hendryadi. (2015). Metode Riset Kuantitatif Teori dan Aplikasipada Penelitian Bidang Manajemen dan Ekonomi Islam. Jakarta: prenadamedia group.